Heroes of the frontier ebook - Eggers, Dave (2016)
A darkly comic and “deeply affecting" tale ( The New York Times ) of a mother and her two young children on a journey through an Alaskan wilderness plagued by wildfires and a uniquely American madness. • From the bestselling author of The Circle. “A picaresque adventure and spiritual coming-of-age tale— On the Road crossed with Henderson the Rain King .” — The New York Times A captivating, often hilarious novel of family and wilderness, this is a powerful examination of our contemporary life and a rousing story of adventure. Josie and her children's father have split up, she's been sued by a former patient and lost her dental practice, and she's grieving the death of a young man senselessly killed shortly after enlisting. When her ex asks to take the children to meet his new fiancée's family, Josie makes a run for it to Alaska with her kids, Paul and Ana. At first their trip feels like a vacation: they see bears and bison, they eat hot dogs cooked on a bonfire, and they spend nights parked along icy cold rivers in dark forests. But as they drive in their rattling old RV, pushed north by the ubiquitous wildfires, Josie is chased by enemies both real and imagined, and past mistakes pursue her tiny family, even to the very edge of civilization.